Programmable Water Jet Show In Aquarium Controlled By PLC - Mohd Faridzan, Azizan (UTeM, 2008)
Programmable Water Jet Show in Aquarium Controlled By PLC was a project develops for the public exhibition. This project will use PLC (Programmable Logic Circuit) as the controller to control the movement of the water jet, lamp, and other accessory in the aquarium. This project can be control by manually and automatically. The water jet can be control in two basic directions which is, forward, and backward and also can be rotate clockwise and anticlockwise. So that people can see the movement of the bubbles in the aquarium. In this project, motors will be use to move the water jet in the aquarium. To make it more interesting, the lamp in the aquarium can be control by selection panel manual and automatic. In this case, four MR16 LED lamps will be use to make it more interesting and it will place at the four angle of the aquarium.